Chemistry : the molecular nature of matter and change - Silberberg, Martin S. (Martin Stuart) 1945- (McGraw-Hill Higher Education, 2009)
Contains macroscopic to microscopic molecular illustrations, consistent step-by-step worked exercises in every chapter, and an extensive range of end-of-chapter problems which provide engaging applications covering a wide variety of freshman interests, including engineering, medicine, materials, and environmental studies.